Predicting financial crises in a globalized world: The case of the Turkish banking sector - (:unkn) unknown (IGI Global, 2018)
This chapter highlights the facts about financial crises and their fundamental causes on specific incidents, including the 1929 Great Depression that lasted until the early-1940s, 1997 Asian Financial Crises, 1998 Russian Financial Crises, and the Liquidity Crises of 2008, and makes a comparison among them and their various outcomes. In doing so, the study specifies the cues that emerge in the financial system that may help governments predict upcoming financial crises through those early warning signals. This case study specifically analyses the Turkish Banking System that was restructured after the enormous financial crises in Turkey in 2001, which caused many Turkish banks to collapse. However, the precautions taken in the aftermath of the financial turmoil allowed them to survive the liquidity crises in 2008. The indicators of an upcoming crisis are examined, the lessons learned from this case are analyzed, and important recommendations to overcome banking crises are provided. © 2018, IGI Global.